A Cause Analysis of the High-Content Nitrogen and Low-Content Hydrocarbon in Shale Gas: A Case Study of the Early Cambrian in Xiuwu Basin, Yangtze Region - Yizhou Huang; Kun Zhang; Zhenxue Jiang; Yan Song; Shu Jiang; Chengzao Jia; Weiwei Liu; Ming Wen; Xuelian Xie; Tianlin Liu; Xin Li; Xin Wang; et al. (Geofluids)
There are successes and failures in the exploration of marine shale gas in South China. In some shale gas plays with great basis for hydrocarbon generation, a phenomenon exists that gas loggings reflect low gas bearing in some of the wells and the gas is dominated by nitrogen rather than hydrocarbon gas. The study of nitrogen concentration in shale gas contributes to solve the question that how shale gas diffuses in complex tectonic areas, which helps to figure out the preservation requirements and accumulation mechanisms of shale gas and avoid exploration crisis. This study focused on the lower Cambrian shale in Xiuwu Basin, Lower Yangtze Region, with emphasis on the well Jiangye-1, using gas component analysis, stable nitrogen isotope analysis, overburden permeability tests in parallel and perpendicular directions, and FIB-HIM experiments, also combining with core description, outcrop observation, and seismic interpretation to explore the causes of the high-content nitrogen and low-content hydrocarbon in the lower Cambrian shale gas. The results show that the nitrogen of the lower Cambrian shale in Xiuwu Basin is derived from the atmosphere and the deep crust-upper mantle. The bedding planes and the detachment layer at the bottom of the lower Cambrian compose the lateral pathways, and the widespread deep faults are the vertical pathways for shale gas migration and diffusion. Combining these two, an effective pathway network was built, favorable to gas exchange between the shale gas interval and the atmosphere, partly leading to the concentration of nitrogen and the diffusion of hydrocarbon gas. In the Jurassic, the magmatic activities occurred frequently in the surrounding areas, which not only brought nitrogen from the deep crust-upper mantle but also increased the value of paleo-heat flow even though the basin began to uplift, which promoted the graphitization of organic matter and the collapse of organic pores and accelerated the loss of shale gas. Based on the study above, an explanation model was summarized to expound the causes of high-content nitrogen and low-content hydrocarbon in shale gas plays near the plate-active region in Xiuwu Basin, Lower Yangtze Region.